SIFAT ANATOMI KAYU BAKAU (Rhizophora mucronata LAMK) - Sushardi; Kodi, Hala (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2018)
Mangrove is one type of mangrove forest plants that has enormous potential and benefits. Almost all parts of mangrove plants can be used; the leaves are for medicine, the skin is for producing tanners and wood for charcoal, building materials and so on. To make more optimal use of mangrove wood, a close study of the properties of the wood is needed. Therefore, knowing the dimensions and value of mangrove fiber derivatives is a very important thing to do. This study aims to determine the dimensions and values of mangrove wood derivatives and their possible uses.The study used a completely randomized factorial design with Tukey's further tests. The factors used are the location of the trunk axial direction (base, middle and tip) and radial direction (near the heart and near the skin). The parameters observed included fiber length, fiber wall thickness, lumen diameter, fiber diameter and fiber dimension derivative values.The results showed that the average value of fiber length was 0.67 mm, fiber wall thickness was 4.25 µ, lumen diameter was 6.71 µ, fiber diameter was 13.83 µ. The average value of fiber dimension derivatives is; runkel number 1.29, muhlsteph number 77.23%, weaving power 10.46, sensitivity coefficient 0.31, and flexibility value 0.48. Based on the value of fiber quality and its derivative value, in general mangrove wood includes the quality of pulp and paper class III, where wood fibers are short to medium size, cell walls and medium lumens. Keywords: Dimensions and values of fiber derivatives, mangrove wood